The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.4137/cmped.s9539
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Difference in the Prevalence of Asthma in the Urban and Rural Environment

Abstract: Multiple risk factors can be modified to decrease asthma incidence. It is important to understand early risks to decrease exposure to harmful conditions in the environment that can trigger asthma which may not be clinically evident in children until they reach adulthood. A retrospective literature review of articles on the prevalence of asthma in the urban versus rural environment was initiated in order to understand the effect of the environment on asthma. The urban-living effect is a global problem in the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 35 publications
(57 reference statements)
2
14
0
Order By: Relevance
“…For example, asthma is a common condition, affecting 1 in 9 school‐aged children . Although pediatric asthma may not be more prevalent in rural versus urban communities in the United States, data indicate that rural children in the United States are more likely than urban children to have uncontrolled asthma, be hospitalized for asthma, and receive inferior care for asthma . Our finding that rural school nurses were less likely than metropolitan nurses to have had recent continuing education on asthma suggests a lack of access to trained health care providers for rural children with asthma.…”
Section: Discussionmentioning
confidence: 73%
“…For example, asthma is a common condition, affecting 1 in 9 school‐aged children . Although pediatric asthma may not be more prevalent in rural versus urban communities in the United States, data indicate that rural children in the United States are more likely than urban children to have uncontrolled asthma, be hospitalized for asthma, and receive inferior care for asthma . Our finding that rural school nurses were less likely than metropolitan nurses to have had recent continuing education on asthma suggests a lack of access to trained health care providers for rural children with asthma.…”
Section: Discussionmentioning
confidence: 73%
“…Thus it appears that there may be a link between the development of hypersensitivity diseases and the urbanization or modernization of society [23]. Many urban environments have similar characteristics (lower air quality, higher population density, lower economic status) that predispose populations to asthma; and similar to the geographical disparity of this disease, rural areas with comparable environments do report greater incidences of hypersensitivity diseases [24, 25]. There is also the possibility that urbanization does not support optimal immune development due to a decrease in exposure to environmental microbes as humans shift from an outdoor lifestyle to a more indoor lifestyle that is characteristic of urban societies [26].…”
Section: ‘The Post-industrial Epidemic’mentioning
confidence: 99%
“…While past research indicated that asthma prevalence may be lower for children living on or near farms (Reidler et al 2001; Gergen et al 1988), recent investigations suggest that asthma morbidity in the rural US is as high or higher than in urban communities (Chrischilles et al 2004; Pesek et al 2010; Malik et al 2012). Rural communities often face unique barriers to asthma diagnosis and management, such as limited access to health care, poor insurance coverage, poverty, and geographic isolation (Valet et al 2009; Ownby 2005).…”
Section: Introductionmentioning
confidence: 99%